THE CORPORATE SPIN-OFF: An Examination of Islamic Banking Legal and Regulatory Framework - Wardah Yuspin; Baskoro Tri Pamungkas; Kelik Wardiono; Mutimatun Ni'ami; Syaifuddin Zuhdi (Jurisdictie: Jurnal Hukum dan Syariah, 2023)
This paper aims to instigate the implementation of Article 68 of the Islamic Banking Act, which obliges Islamic divisions to be separated from their parent banks. This study attempted to reveal a legal solution so that the obligations can be turned into a corporate action. The argument presented by a critical review approach based on a literature review using secondary data. The solution still considers spin-offs a necessity, not a mandate. It is supposed to be considered a corporate action that its implemented based on readiness so the article needs to be amended. This paper proposes changes to the article on spin-offs for the development of Islamic Banking in Indonesia with practical benefits. Alternative changes can be completed in three ways: first, by issuing Financial Services Authority Regulation (FSAR), which makes the spin-off a corporate action. This method is unconstitutional because FSAR is structurally under the Constitution. The second alternative is done by submitting a judicial review of Article 68 to the Constitutional Court. Finally, the third is by enacting the omnibus law of Islamic economics. Those three options have both advantages and disadvantages. Thus, it is necessary to further find out which solution is most prospective for advancing Islamic banking.Artikel ini bertujuan untuk mendorong penerapan Pasal 68 Undang-Undang Perbankan Syariah yang mewajibkan divisi syariah dipisahkan dari bank induknya. Kajian ini mencoba mengungkap solusi hukum agar kewajiban tersebut dapat berubah menjadi aksi korporasi. Argumen yang disajikan menggunakan pendekatan Solusinya tetap menganggap spin off sebagai kebutuhan, bukan sebagai mandat. Hal ini seharusnya dianggap sebagai corporate action yang pelaksanaannya berdasarkan kesiapan sehingga pasal tersebut perlu diubah. Makalah ini mengusulkan perubahan pasal spin-off untuk perkembangan perbankan syariah di Indonesia dengan manfaat praktis. Alternatif perubahan bisa dilakukan dengan tiga cara, pertama dengan menerbitkan Peraturan Otoritas Jasa Keuangan (POJK) yang menjadikan spin off sebagai corporate action. Cara ini inkonstitusional karena POJK secara struktural berada di bawah konstitusi. Alternatif kedua dilakukan dengan mengajukan uji materi pasal 68 ke Mahkamah Konstitusi. Terakhir, yang ketiga adalah dengan pengundangan omnibus law ekonomi syariah. Ketiga pilihan tersebut memiliki kelebihan dan kekurangan. Untuk itu perlu dikaji lebih lanjut solusi mana yang paling prospektif untuk memajukan perbankan syariah.